2008
DOI: 10.1177/1368430207084849
|View full text |Cite
|
Sign up to set email alerts
|

`They Cooperate With Us, So They Are Like Me': Perceived Intergroup Relationship Moderates Projection from Self to Outgroups

Abstract: Whereas projection of self-attributes to ingroups is ubiquitous, projection of self-attributes to outgroups (outgroup projection) is an elusive phenomenon. Two experiments examined the moderating effect of perceived intergroup relationship on outgroup projection and explored underlying mechanisms. Perceived cooperation versus competition between ingroup and outgroup was manipulated using fictitious (Experiment 1) or natural groups (Experiment 2). In both experiments, participants judged the outgroup as more si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 30 publications
5
47
0
Order By: Relevance
“…Cooperation, Competition and Interpersonal Projection 17 outgroup projection had already shown that perceived intergroup interdependence moderates projection (Riketta & Sacramento, 2008) and that positive ingroup-outgroup contacts increase outgroup projection (Stathi & Crisp, 2008). The current experiments extend this work to the interpersonal level.…”
Section: Accepted Manuscriptsupporting
confidence: 59%
See 2 more Smart Citations
“…Cooperation, Competition and Interpersonal Projection 17 outgroup projection had already shown that perceived intergroup interdependence moderates projection (Riketta & Sacramento, 2008) and that positive ingroup-outgroup contacts increase outgroup projection (Stathi & Crisp, 2008). The current experiments extend this work to the interpersonal level.…”
Section: Accepted Manuscriptsupporting
confidence: 59%
“…These traits were borrowed from Riketta and Sacramento (2008) who pretested them to be unrelated to cooperation and competition. Participants had to indicate the extent to which each of the traits (e.g., progressive, silent, creative) characterized them on a 9-point rating scale ranging from 1 (= not at all) to 9 (= very much).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, more social projection is observed in cooperative contexts both at the interpersonal and intergroup levels. At the intergroup level, Riketta and Sacramento (2008) found that people are more likely to see an outgroup as similar to themselves if it is cooperating rather than competing with the ingroup. At the interpersonal level, Toma et al (2010) recently showed that people see a target person as more similar to themselves when they anticipate cooperation rather than competition with the target person.…”
Section: Self-other Similarity In Construing the Ideal Partnermentioning
confidence: 96%
“…These traits, borrowed from Riketta and Sacramento (2008), represent four of the Big Five personality traits (extraversion, emotional stability, agreeableness, and openness to Running head: POWER AND INTERPERSONAL PROJECTION 6 experience; four adjectives for each trait). Participants had to indicate the extent to which each of the traits (e.g., progressive, sociable, slow) characterized them.…”
Section: Methodsmentioning
confidence: 99%